2021
DOI: 10.1186/s12885-021-07814-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted RNAseq assay incorporating unique molecular identifiers for improved quantification of gene expression signatures and transcribed mutation fraction in fixed tumor samples

Abstract: Background Our objective was to assess whether modifications to a customized targeted RNA sequencing (RNAseq) assay to include unique molecular identifiers (UMIs) that collapse read counts to their source mRNA counts would improve quantification of transcripts from formalin-fixed paraffin-embedded (FFPE) tumor tissue samples. The assay (SET4) includes signatures that measure hormone receptor and PI3-kinase related transcriptional activity (SETER/PR and PI3Kges), and measures expression of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Sequencing was performed using Illumina HiSeq 4000 (Illumina, San Diego, California), with six libraries pooled per lane. Targeted RNA‐seq libraries were prepared incorporating unique molecular identifier (UMI) sequences to label individual mRNA molecules during reverse transcription and a customized droplet‐based protocol for amplification of complementary DNA (cDNA), as described previously 20 . RNA was reverse‐transcribed using UMI‐labeled gene‐specific primers to target the regions of interest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing was performed using Illumina HiSeq 4000 (Illumina, San Diego, California), with six libraries pooled per lane. Targeted RNA‐seq libraries were prepared incorporating unique molecular identifier (UMI) sequences to label individual mRNA molecules during reverse transcription and a customized droplet‐based protocol for amplification of complementary DNA (cDNA), as described previously 20 . RNA was reverse‐transcribed using UMI‐labeled gene‐specific primers to target the regions of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Targeted RNA-seq libraries were prepared incorporating unique molecular identifier (UMI) sequences to label individual mRNA molecules during reverse transcription and a customized droplet-based protocol for amplification of complementary DNA (cDNA), as described previously. 20 RNA was reverse-transcribed using UMI-labeled gene-specific primers to target the regions of interest. Purified cDNA was added to a polymerase chain reaction (PCR) master mix and distributed among millions of pico-liter sized droplets using RainDance Source system…”
Section: Whole-transcriptome and Targeted Rna-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…For PIK3CA and TILs gene signatures, raw intensity files (.CEL) from each microarray were processed using MAS5.0 to generate probe-level intensities and normalized to a median array intensity of 600, transformed to log2 values, and scaled by the expression levels of 1322 breast cancer reference genes within each sample normalized to median values in a reference cohort 35 . Two PIK3CA-related gene signatures were calculated for each microarray: first, a PIK3CA gene signature that measures transcriptional activity associated with PI3KCA mutation 41 , and secondly, a modification of that first signature that includes only the probe sets robust to technical variation and variation due to tumor heterogeneity 42 . Two TIL gene signatures were calculated for each microarray: a gene signature trained on TIL infiltrate (calculated as the mean gene expression of IGKC, CXCL9, CCL5, and TRBC1 minus the mean gene expression of AK2, APPBP2, ATP5MF, DARS1, LDHA, TRIM2, UBE2Z, UGP2, VDAC2, and WIPF2WIPF2), and a signature to predict high TILs after subsequent neoadjuvant chemotherapy 43 .…”
Section: Methodsmentioning
confidence: 99%
“…The assay also measures selected point mutations in AKT1, PTEN, and ERBB2, and measures the expression level of other single genes (ESR1, PGR, ERBB2, AURKA, FRFR1). 17 We previously demonstrated that two common cytological preparations of malignant effusion specimens (cytospins fixed in Carnoy's solution and cytospins fixed in 95% EtOH) were similar to optimally prepared fresh frozen (FF) high-quality RNA samples stored in an RNA preservative (RNAlater) and superior to cell blocks (FFPE), ThinPrep, SurePath and air-dried Diff-Quik stained cytospins. 8 Therefore, we compared the three best preparation methods (ie compared Carnoy's solution and 95% EtOH fixed cytospins with FF cell pellet) at different durations of refrigerated storage (day 0, 1, 4, and 7) using wtRNAseq and tRNAseq to measure two multigene expression signatures (SET ER/PR and PI3Kges), molecular subtype, and common activating mutations.…”
mentioning
confidence: 99%